Structural complexity in Prussian blue analogues. Issue 12 (29th October 2021) - Cattermull, John; Pasta, Mauro; Goodwin, Andrew L.
Abstract : We survey the most important kinds of structural complexity in Prussian blue analogues and their implications for materials function. In particular, we explore the challenges for K2 Mn[Fe(CN)6 ], the leading cathode material for K-ion batteries. Abstract : We survey the most important kinds of structural complexity in Prussian blue analogues, their implications for materials function, and how they might be controlled through judicious choice of composition. We focus on six particular aspects: octahedral tilts, A-site 'slides', Jahn–Teller distortions, A-site species and occupancy, hexacyanometallate vacancies, and framework hydration. The promising K-ion cathode material K x Mn[Fe(CN)6 ] y serves as a recurrent example that illustrates many of these different types of complexity. Our article concludes with a discussion of how the interplay of various distortion mechanisms might be exploited to optimise the performance of this and other related systems, so as to aid in the design of next-generation PBA materials.